2011
DOI: 10.1002/btpr.739
|View full text |Cite
|
Sign up to set email alerts
|

Neurite outgrowth of PC12 cells on diX (parylene) family materials

Abstract: We investigated neuronal cell differentiation, particularly neurite outgrowth, on the surface of diX H and diX AM using an in vitro examination of a neuron-like rat pheochromocytoma cell line, PC12. diX H and diX AM are in the parylene family of diX C (or Parylene-C), which is widely used as a novel coating material to insulate neural electrodes, and they have been recently commercialized; diX H and diX AM offer different features of biocompatibility. Previously, we found that these new parylene materials have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recently, some new parylene polymers have been used on tissue engineering and biosensor for neuron adhesive growth in culture. These polymers [poly‐chloro‐para‐xylylene (diX C), poly‐monoaminomethyl‐para‐xylylene (diX AM), and poly‐monoaldehyde‐para‐xylylene (diX H)] can be coated on SiO 2 surface in combination with proteins and UV irradiation and have been shown to markedly improve the neuronal cell attachment on micropatterned surfaces 10–13…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some new parylene polymers have been used on tissue engineering and biosensor for neuron adhesive growth in culture. These polymers [poly‐chloro‐para‐xylylene (diX C), poly‐monoaminomethyl‐para‐xylylene (diX AM), and poly‐monoaldehyde‐para‐xylylene (diX H)] can be coated on SiO 2 surface in combination with proteins and UV irradiation and have been shown to markedly improve the neuronal cell attachment on micropatterned surfaces 10–13…”
Section: Introductionmentioning
confidence: 99%
“…Kato et al observed no cell attachment to parylene-C or parylene-A, however, cell attachment was observed to parylene-AM and parylene-H. This work was expanded on by Hoshino et al who examined the outgrowth of neurites from PC12 cells on parylene-AM and parylene-H [50]. Hoshino et al found that neurite outgrowth was greatest on the parylene-H.…”
Section: Resultsmentioning
confidence: 99%